2020
DOI: 10.1542/peds.2020-0531
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth Home Monitoring and Postcardiac Surgery for Congenital Heart Disease

Abstract: OBJECTIVES:To test the effect of a 4-month telehealth home monitoring program (REACH), layered on usual care, on postdischarge outcomes in parents of infants recovering from cardiac surgery and their infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…Another recent publication sheds additional insight on the growth pattern of these infants in the first few months of life [15 ▪ ]. As part of a trial of telehealth home monitoring program in neonates undergoing cardiac surgery, weekly weights were measured for the first 4 months of life [16]. Of 178 infants included in this study, 95 or 53% had univentricular physiology.…”
Section: Prevalence Of Feeding Challenges and Growth Failurementioning
confidence: 99%
“…Another recent publication sheds additional insight on the growth pattern of these infants in the first few months of life [15 ▪ ]. As part of a trial of telehealth home monitoring program in neonates undergoing cardiac surgery, weekly weights were measured for the first 4 months of life [16]. Of 178 infants included in this study, 95 or 53% had univentricular physiology.…”
Section: Prevalence Of Feeding Challenges and Growth Failurementioning
confidence: 99%
“… 38 , 39 However, some research has shown that increased home monitoring may not result in improved outcomes and may even increase healthcare utilization given the closer monitoring and more convenient access to care. 40 Additionally, while patient-generated measurements have the potential to increase the provider confidence and support a shift to alternating or supplementing in-person and telemedicine visits, parents may have low self-efficacy with regard to home measurements. 23 , 31 Thus, appropriate training of caregivers and better evidence are necessary to ensure successful use of home monitoring devices and a positive caregiver experience.…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced family management of children with single ventricle physiology can be leveraged to improve health outcomes, care transitions, and quality of life for both children and caregivers (Grey et al, 2006, 2015; Valdez et al, 2020). An important part of the integrated family management framework includes home monitoring and communication during the vital interstage period (Medoff Cooper et al, 2020). Current strategies used in home monitoring depend on the caregivers' ability to document daily records of oxygen saturation, daily weights, feeding tolerance, and respond to intermittent telephone communication for an extended period of time (often 6 months or more).…”
Section: Discussionmentioning
confidence: 99%
“…There has been an increased attention in home monitoring technology and mobile applications over the past several years that have demonstrated promising results (Bingler et al, 2018; Erickson et al, 2020; Foster et al, 2021; Medoff Cooper et al, 2020; Nkoy et al, 2019). There is a need to continue to push the state of the science beyond the advantages in home monitoring to the implementation science aspects of (1) determining the best way to design home monitoring systems that allow caregivers and patients to actively participate in their data entry and communication with providers, (2) implementation of technology‐enhanced home monitoring that promotes adherence to data entry, and (3) assessment of how technology‐enhanced home monitoring can contribute to clinical‐decision making of providers by responding to changes in patient situations based on established algorithms and nuanced trends in clinical data.…”
Section: Discussionmentioning
confidence: 99%